The use of electrocardiogram screening to clear athletes for return to sport following COVID-19 infection - Erickson, J. L.; Poterucha, J. T.; Gende, A.; McEleney, M.; Wencl, C. M.; Castaneda, M.; Gran, L.; Luedke, J.; Collum, J.; Fischer, K. M.; Jagim, A. R. (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2021)
Objective: To quantify the occurrence rate of abnormal ECG findings and symptoms following COVID-19 infection. Patients: Adult patients (>18 years old) who were participating in collegiate athletics and previously tested positive for COVID-19 between August 2020 to November 2020. Methods: In this retrospective study, we report findings of electrocardiogram (ECG) testing to screen athletes for cardiac abnormalities following COVID-19. Athletes underwent general examinations and ECG screening prior to being medically cleared for a return to sport following COVID-19. Predetermined predictors were grouped into categorical variables including: 1) Sex; 2) Symptom severity; and 3) BMI (normal vs. overweight = > 24 kg·m-2). These were used to examine differences of abnormal rates occurred between different predictor categories. Results: Of the 170 athletes screened, 6 (3.5%) presented with abnormal ECG criteria and were referred to cardiology. We found no evidence that symptom severity, sex and BMI category were associated with a higher rate of abnormal ECG (p > 0.05). Greater severity of COVID-19 symptoms were associated with higher percentage of ST depression, T-wave inversion, ST-T changes and presence of fQRS. Loss of smell, loss of taste, headache and sore throat were the most prevalent symptoms with 32.9%, 38.8%, 36.5% and 25.3% of athletes reporting each symptom, respectively.Conclusions: Preliminary findings indicate a low risk of myocardial injury secondary to COVID-19 infection with less than4% of patients presenting with abnormal ECG and 10% requiring referral to a cardiologist. While viral myocarditis was not demonstrated in any athlete referred for cardiology assessment, two patients developed effusative viral pericarditis.